2002
DOI: 10.1074/jbc.m203097200
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-Linked Oligosaccharide Flexibility in Mannose Phosphorylation of Lysosomal Enzyme Cathepsin L

Abstract: Mannose phosphorylation of N-linked oligosaccharides by UDP-GlcNAc:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase is a key step in the targeting of lysosomal enzymes in mammalian cells and tissues. The selectivity of this process is determined by lysine-based phosphorylation signals shared by lysosomal enzymes of diverse structure and function. By introducing new glycosylation sites at several locations on the surface of mouse procathepsin L and modeling oligosaccharide conformations for sites that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This can be explained if some of the glycans have unfavorable locations on the surface of the hydrolase relative to the site of the protein recognition domains where GlcNAc-1-phosphotransferase docks. Presumably only glycans within a certain range of the docking site will be able to engage the catalytic elements of the transferase (34,35). We have previously speculated that binding of the ␥MRH domain to selected high mannose glycans with unfavorable locations may FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained if some of the glycans have unfavorable locations on the surface of the hydrolase relative to the site of the protein recognition domains where GlcNAc-1-phosphotransferase docks. Presumably only glycans within a certain range of the docking site will be able to engage the catalytic elements of the transferase (34,35). We have previously speculated that binding of the ␥MRH domain to selected high mannose glycans with unfavorable locations may FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that acid hydrolases with multiple N-linked glycans exhibit considerable variability in the extent of phosphorylation at the individual sites (44 -48). It has also been found that the introduction of new glycosylation sites on several acid hydrolases results in variable degrees of phosphorylation (24,49). These findings can be explained if the location of the N-linked glycans on the surface of the hydrolases varies relative to the position of the protein recognition domain.…”
Section: Discussionmentioning
confidence: 99%
“…If GNPTG would function in recognition of lysosomal hydrolases, its overexpression should impair sorting which subsequently results in hypersecretion of newly synthesized lysosomal enzymes into media. Because we have neither observed an increase in the secretion of metabolically labelled cathepsin D nor in the activities of three lysosomal enzymes in the media of GNPTG overexpressing cells, we hypothesize that GNPTG lacks the capability to bind to a conformation-dependent recognition domain present on the surface of many different lysosomal enzymes [24][25][26][27][28]. This hypothesis is supported by our previous studies demonstrating that no lysosomal enzymes could be eluted from a GNPTG affinity matrix [6].…”
Section: Accepted Manuscriptmentioning
confidence: 59%